Exploding the Hearth: Considering Victorian Aging - Palmor, Lauren (Age, Culture, Humanities: An Interdisciplinary Journal, 2015)
The image of the aged parent or grandparent sitting contentedly before the hearth is a canonical trope in Victorian visual culture. The freside was, at that time, a signifcant center of the home and family, and older members of the household were viewed as principal organizing forces around this central gathering place. This article examines the archetypal image of the senescent hearthside fgure in order to better evaluate the larger context in which Victorian aging was visually interpreted and generally understood. By examining depictions of this theme by the popular British painters Walter Dendy Sadler and Frederick Daniel Hardy, this study demonstrates some ways in which art history may proft from age studies in formulating expanded readings of such material.